Climate change, snow mold and the Bromus tectorum invasion: mixed evidence for release from cold weather pathogens. Issue 5 (16th July 2019) - Smull, Danielle M; Pendleton, Nicole; Kleinhesselink, Andrew R; Adler, Peter B
Abstract: Climate change is reducing the depth and duration of winter snowpack, leading to dramatic changes in the soil environment with potentially important ecological consequences. Previous experiments in the Intermountain West of North America indicated that loss of snowpack increases survival and population growth rates of the invasive annual grass Bromus tectorum ; however, the underlying mechanism is unknown. We hypothesized that reduced snowpack might promote B. tectorum population growth by decreasing damage from snow molds, a group of subnivean fungal pathogens. To test this hypothesis, we conducted greenhouse and field experiments to investigate the interaction between early snowmelt and either fungicide addition or snow mold infection of B. tectorum . The greenhouse experiment confirmed that the snow mold Microdochium nivale can cause mortality of B. tectorum seedlings. In the field experiment, early snowmelt and fungicide application both increased B. tectorum survival, but their effects did not interact, and snow mold inoculation had no effect on survival. We did find interactive effects of snowmelt and fungal treatments on B. tectorum seed production: with ambient snowpack, M. nivale inoculation reduced seed production and fungicide increased it, whereas in the early snowmelt treatment seed production was high regardless of fungal treatment. However, treatment effects on seed production did not translate directly to overall population growth, which did not respond to the snow melt by fungal treatment interaction. Based on our mixed results, the hypothesis that reduced snowpack may increase B. tectorum fitness by limiting the effects of plant pathogens deserves further investigation. Abstract : Climate change and biological invasions are two primary drivers of global change. They can also have interactive effects. We studied the potential for climate change to promote the growth of a destructive invasive annual grass, Bromus tectorum, by reducing snow pack and releasing the plant from snow mold infections. We found evidence that snow molds do limit seed production but not survival or overall population growth. The potential for climate change to reduce the impact of cold weather pathogens deserves further investigation.